Distribution of Divo in Coffea genomes, a poorly described family of angiosperm LTR-Retrotransposons - Dupeyron, Mathilde (2017)
Coffea arabica (the Arabica coffee) is an allotetraploid species originating from a recent hybridization between two diploid species: C. canephora and C. eugenioides. Transposable elements can drive structural and functional variation during the process of hybridization and allopolyploid formation in plants. To learn more about the evolution of the C. arabica genome, we characterized and studied a new Copia LTR-Retrotransposon (LTR-RT) family in diploid and allotetraploid Coffea genomes called Divo. It is a complete and relatively compact LTR-RT element (~5 kb), carrying typical Gag and Pol Copia type domains. Reverse Trancriptase (RT) domain-based phylogeny demonstrated that Divo is a new and well-supported family in the Bianca lineage, but strictly restricted to dicotyledonous species. In C. canephora, Divo is expressed and showed a genomic distribution along gene rich and gene poor regions. The copy number, the molecular estimation of insertion time and the analysis at orthologous locations of insertions in diploid and allotetraploid coffee genomes suggest that Divo underwent a different and recent transposition activity in C. arabica and C. canephora when compared to C. eugenioides. The analysis of this novel LTR-RT family represents an important step toward uncovering the genome structure and evolution of C. arabica allotetraploid genome.